Strategi Bisnis Waterpark PTC Jayapura dalam Meningkatkan Keuntungan Usaha - Weny Lestari Sinaga; Candraningrat (Economic Reviews Journal, 2024)
Business strategy can be measured as good and bad using five business strategy indicators, namely marketing, operations, distribution, organization and strategies related to finance. Likewise with the Waterpark business strategy that is implemented to increase profits. The aim of this Scientific Work is to determine the PTC Jayapura Waterpark business strategy in increasing business profits. The research method used is descriptive qualitative. The research results obtained are that the PTC Jayapura Waterpark business strategy in increasing business profits has been implemented in accordance with five business strategy indicators, namely (1) marketing, (2) operations (3) distribution, (4) organization, and (5) related strategies with finances. The business strategy implemented can be said to be able to increase finances because the management has been carried out semi-professionally. This is stated because, even though the business being run is not yet in the form of a PT/CV, Waterpark PTC has carried out a business strategy in a precise and efficient manner, so as to increase profits from business activities